2002
DOI: 10.1002/bdd.330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concomitant colestipol hydrochloride administration on the bioavailability of diltiazem from immediate‐ and sustained‐release formulations

Abstract: Effects of concomitant colestipol administration on plasma concentrations of diltiazem and desacetyldiltiazem from immediate-release (IR) and sustained-release (SR) formulations were assessed in two studies. In the first study, 12 subjects received 120-mg diltiazem hydrochloride (diltiazem) SR capsules or 120-mg diltiazem IR tablets administered alone and in combination with colestipol hydrochloride (colestipol). Following concomitant administration of SR diltiazem with colestipol, AUC(0-infinity ) and C(max),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
0
1
Order By: Relevance
“…Compared with the PK parameters obtained from the same oral dose of tablets, the main PK parameters of t max , C max , AUC t and t 1/2 of diltiazem hydrochloride delayedonset sustained-release pellet capsules in three single oral dose groups were much higher in the present study than the corresponding PK parameters reported in the previous literatures (Murata et al, 1989;Turner, 2002).…”
Section: Discussioncontrasting
confidence: 73%
“…Compared with the PK parameters obtained from the same oral dose of tablets, the main PK parameters of t max , C max , AUC t and t 1/2 of diltiazem hydrochloride delayedonset sustained-release pellet capsules in three single oral dose groups were much higher in the present study than the corresponding PK parameters reported in the previous literatures (Murata et al, 1989;Turner, 2002).…”
Section: Discussioncontrasting
confidence: 73%